Experimental analysis of the state of stress in a steel – titanium perforated plate loaded with concentrated force - Mateusz Konieczny; Grzegorz Gasiak; Henryk Achtelik (Fracture and Structural Integrity)
The paper presents an experimental analysis of the state of stress, free supported on the edge of a steel – titanium circular perforated plate loaded with a centrally concentrated force, created in the technological process of explosion welding. For this purpose, a special test stand was designed and a methodology for testing the perforated plate was developed. Resistance strain gauges were used to measure the state of strain. The load was applied in the center of the plate to a pressure stamp. As a result of the research, the values of radial, circumferential and equivalent von Mises stress were obtained as a function of the radius of the plate perforation circle and its load. The stress distribution topography revealed the zones of maximum stress of the steel – titanium perforated plate. The proposed method of experimental research can be used by engineers to verify the state of stress, e.g. in the designed tube sheet walls of reactors for ammonia synthesis.